Ethnopharmacology of Tribals of Ranchi District in Jharkhand - Ajaz-ul-islam, Mohammad; Masoodi, N. A. (Indian Forester, 2007)
The present paper communicates information on 83 ethno-medicinally important plant species belonging to 77 genera and 41 families and being utilised for 57 common diseases by the tribal people of Ranchi district in Jharkhand. These plants have been arranged alphabetically with their family, vernacular name, plant habit, flowering and fruiting period, plant part used and specific uses. Several of the plant species are likely to go under the category of threatened plant species due to over exploitation and habitat destruction if appropriate scientific conservation measures are not adopted immediately.